Carbon-Source Dependent Interplay of Copper and Manganese Ions Modulates the Morphology and Itaconic Acid Production in Aspergillus terreus - Sándor, Erzsébet; Kolláth, István S.; Fekete, Erzsébet; Bíró, Vivien; Flipphi, Michel; Kovács, Béla; Kubicek, Christian P.; Karaffa, Levente (Frontiers in Microbiology, 2021)
The effects of the interplay of copper (II) and manganese (II) ions on growth, morphology and itaconic acid formation was investigated in a high-producing strain of Aspergillus terreus (NRRL1960), using carbon sources metabolized either mainly via glycolysis (D-glucose, D-fructose) or primarily via the pentose phosphate shunt (D-xylose, L-arabinose). Limiting Mn2+ concentration in the culture broth is indispensable to obtain high itaconic acid yields, while in the presence of higher Mn2+ concentrations yield decreases and biomass formation is favored. However, this low yield in the presence of high Mn2+ ion concentrations can be mitigated by increasing the Cu2+ concentration in the medium when D-glucose or D-fructose is the growth substrate, whereas this effect was at best modest during growth on D-xylose or -arabinose. A. terreus displays a high tolerance to Cu2+ which decreased when Mn2+ availability became increasingly limiting. Under such conditions biomass formation on D-glucose or D-fructose could be sustained at concentrations up to 250 mg L-1 Cu2+, while D-xylose- or L-arabinose supported growth was fully inhibited already at 100 mg L-1, while on D-xylose- or L-arabinose biomass formation was completely inhibited at 100 mg L-1. High (>75%) specific molar itaconic acid yields always coincided with an “overflow-associated” morphology, characterized by small compact pellets (<250 mm diameter) and short chains of “yeast-like” cells that exhibit increased diameters relative to the elongated cells in growing filamentous hyphae. At low concentrations (≤1 mg L-1) of Cu2+ ions, manganese deficiency did not prevent filamentous growth. Mycelial- and cellular morphology progressively transformed into the typical overflow-associated one when external Cu2+ concentrations increased, irrespective of the available Mn2+. Our results indicate that copper ions are relevant for overflow metabolism and should be considered when optimizing itaconic acid fermentation in A. terreus.